2003
DOI: 10.1159/000073057
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Driving Performance in Patients with Relapsing-Remitting Multiple Sclerosis by a Driving Simulator

Abstract: Objective: To compare the driving performance using a driving simulator with physical and cognitive functions as measured by the Expanded Disability Status Scale (EDSS) and the Multiple Sclerosis Functional Composite (MSFC) in patients suffering from the relapsing-remitting form of multiple sclerosis (RRMS). Methods: 31 RRMS patients (18 women, 13 men, mean age 35.6 ± 8.3 years, EDSS 2.8 ± 1.4) were compared with 10 healthy controls (8 men, 2 woman, age 45.1 ± 7.8 years). Results: Compared with controls, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 11 publications
(13 reference statements)
4
41
0
2
Order By: Relevance
“…As no published results of sequential testing were available at the time of the study, sample size calculation was based on the following assumptions. For the neuropsychological testing, mean alertness reaction time was expected to be 431 ms with SD of 15% (60.6 ms) [21]. The study was then designed to establish a difference of 15% with an a-error of 5% and a b-error of 10% (minimal required sample size: n522).…”
Section: Methodsmentioning
confidence: 99%
“…As no published results of sequential testing were available at the time of the study, sample size calculation was based on the following assumptions. For the neuropsychological testing, mean alertness reaction time was expected to be 431 ms with SD of 15% (60.6 ms) [21]. The study was then designed to establish a difference of 15% with an a-error of 5% and a b-error of 10% (minimal required sample size: n522).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that driving simulators are useful in the evaluation of on-road driving abilities of older individuals (Freund et al, 2002;Lee, Lee, 2005) and after neurological impairments (Kotterba et al, 2003;Devos et al, 2007). Some driving skills commonly assessed during simulator-based driving evaluations include lane tracking, gap estimation (time and range to collision), accident avoidance, compliance with speed limits and reaction time.…”
Section: Introductionmentioning
confidence: 99%
“…An early intervention is in fact desirable for the benefits it can have on both clinical and neural outcomes, while delayed intervention can carry the risk of irreversible damage. An early intervention can indeed slow the progression of the disease and have effects on the quality of life of both patients and families, considering that cognitive deficits, and particularly deficits of verbal memory, information processing speed and executive functions, can predict professional status (Benedict et al, 2006) and have a significant impact on complex tasks in the home and on driving (Shawaryn et al, 2002;Kotterba et al, 2003;Schultheis et al, 2002). Moreover, clinical investigations have indicated that early intervention with disease-modifying therapies may help to prevent permanent damage, and appears to reduce the frequency and severity of clinical attacks, slow the accumulation of disability, and reduce the development of new lesions.…”
Section: Discussionmentioning
confidence: 99%